Graduates' vocational skills for the management accountancy profession: exploring the accounting education expectation-performance gap - Howcroft, Douglas (Taylor & Francis, 2017)
This paper focuses on understanding the vocational skills required by graduates and assessing the competence of graduates for the management accountancy profession. It explores ‘expectation gaps’ by examining whether the Chartered Institute of Management Accountants (CIMA), practitioner employers and university educators have different expectations with regard to the important vocational skills for graduates. The research aim is to generate a greater understanding of the factors that create identified expectation gaps between the above stakeholders and to explore the implications of any gaps.